Regulatory flexibilities and access to COVID-19 vaccines during the pandemic in Bhutan - Tshering, Dawa; Chejor, Pelden (Exploratory research in clinical and social pharmacy, 2022)
Coronavirus disease 2019 (COVID-19) is rapidly evolving with millions of cases and death reported globally. The first-ever case of COVID-19 in Bhutan was confirmed on 5 March 2020 in a 76-year-old American tourist. The national regulatory authorities have implemented varying degrees of regulatory flexibilities to prevent unnecessary death by ensuring timely access to medical products and technologies during the pandemic. The Drug Regulatory Authority of Bhutan, as a national medicines regulatory agency responsible for ensuring the quality of medical products has implemented several regulatory mechanisms to ensure access to medical products including COVID-19 vaccines during the pandemic. In this commentary, we discuss the regulatory flexibilities that ensured access to medical products and COVID-19 vaccines during the pandemic.Coronavirus disease 2019 (COVID-19) is rapidly evolving with millions of cases and death reported globally. The first-ever case of COVID-19 in Bhutan was confirmed on 5 March 2020 in a 76-year-old American tourist. The national regulatory authorities have implemented varying degrees of regulatory flexibilities to prevent unnecessary death by ensuring timely access to medical products and technologies during the pandemic. The Drug Regulatory Authority of Bhutan, as a national medicines regulatory agency responsible for ensuring the quality of medical products has implemented several regulatory mechanisms to ensure access to medical products including COVID-19 vaccines during the pandemic. In this commentary, we discuss the regulatory flexibilities that ensured access to medical products and COVID-19 vaccines during the pandemic.